Reconstructing the Climate Variability During the Last 5000 Years From the Banni Plains, Kachchh, Western India - Makwana, Nisarg; Prizomwala, S. P.; Das, Archana; Phartiyal, Binita; Sodhi, Aashima; Vedpathak, Chintan (Frontiers in Earth Science, 2021)
The climatic conditions during the beginning of the last 5000 years have been discussed, debated and documented from various parts of the Indian subcontinent, due to the human-climate interrelationship. In present study, we report a multiproxy dataset encompassing the widely used ~ geochemical and mineral magnetic proxies supported by radiocarbon and optical chronologies from the Banni Plains of the Rann of Kachchh, Western India. Our results support the earlier observations of prolonged wetter climatic condition synchronous with the mature phase of Harappan era which witnessed a short and intense arid condition at the terminal part of the Mature Harappan phase. The climate system dramatically fluctuated during the last five millennia from pulsating between relatively arid (4800 to 4400 yr BP, 3300 - 3000 yr BP and at 2400 yr BP) and relatively humid phases (> 4800 yr BP, 4000 - 3300 yr BP, 1900 - 1400 yr BP and 900 - 550 yr BP). The multiproxy dataset shows a gradual strengthening of the monsoonal conditions from the Banni Plains during the Late Harappan phase. Apart from this, the high sedimentation rate (> 1mm/yr) recorded from the Banni Plains, suggest it can be tapped as a robust archive to reconstruct multidecadal to centennial climatic events spanning the Holocene Epoch.